Water - Walpole, Brenda; Bull, Peter 1960-.; Chen, Kuo Kang. (London Kingfisher Books, 1987)
Examines the properties of water and gives instructions for a variety of experiments using simple materials.
Keywords: Water -- Experiments -- Juvenile literature; Experiments; Water -- Experiments